Generation and management of solid waste in a mechanical workshop - Lima, Michael Bruno Oliveira de; Viana, Ednilson (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Numbers show how important is a mechanical workshop, it is one of the main economics activities of Brazil´s services sector. Due this big quantity and the type of work, we can say that this kind of firm are a big generating of solid waste, and the most important, some of this waste have a large amount of toxic compounds. Therefore, the management and the discard must be done correctly, so there is no effect in the employee´s health and do not contaminate the environment. This work has analyzed a study in one case in Vila Mariana, São Paulo-SP, to diagnose measure and quantify the generation of this waste and your management in a small workshop. After the identification of the wastes they were classified after NBR-10.004 da ABNT, with the purpose of make it easier to analysis. It can be observed a several mistakes in the management of this workshop, in all of the stages, collection, handling, storage, transportation and final discard. It was observed that the management of the wastes is ineffective and problematic, and must be improved through more sector agreements, given the necessary importance for the correct management.